2021
DOI: 10.4064/sm190102-30-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum symmetry of graph $C^{\ast }$-algebras at\cr critical inverse temperature

Abstract: We give a notion of quantum automorphism group of graph C * -algebra without sink at critical inverse temperature. This is defined to be the universal object of a category of CQG's having a linear action in the sense of [11] and preserving the KMS state at critical inverse temperature. We show that this category for a certain KMS state at critical inverse temperature coincides with the category introduced in [11] for a class of graphs. We also introduce an orthogonal filtration on Cuntz algebra with respect to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…In that case, the graph C * -algebra coincides with the Pimsner algebra, allowing us to apply the above results. In particular, we recover the results obtained in [JM21a,JM21b,SW18]. This also enables us to gain a more concrete understanding of most of the results concerning the interaction between quantum symmetries of graphs and its graph C * -algebras.…”
Section: Question 13 Given An Action ρ Of a Compact Quantum Group G O...supporting
confidence: 74%
See 1 more Smart Citation
“…In that case, the graph C * -algebra coincides with the Pimsner algebra, allowing us to apply the above results. In particular, we recover the results obtained in [JM21a,JM21b,SW18]. This also enables us to gain a more concrete understanding of most of the results concerning the interaction between quantum symmetries of graphs and its graph C * -algebras.…”
Section: Question 13 Given An Action ρ Of a Compact Quantum Group G O...supporting
confidence: 74%
“…Similar richness of quantum symmetries has been observed in other contexts as well. For example, compact quantum groups have been found to preserve fewer KMS states on certain graph C * -algebras as opposed to compact group actions [JM21a]. As a necessarily incomplete list of references for the reader interested in this direction, we mention [Gab14,GW16,Kat17,Pao97].…”
Section: Compact Quantum Group Actions On Pimsner Algebrasmentioning
confidence: 99%
“…For , we have . So By the same argument as given in the proof of the Theorem 3.5 of [8], for , and hence the last expression equals to Observe that any state restricts to a state on so that by Lemma 2.32, for , . Using this, the last summation reduces to Using the same arguments used in the proof of Theorem 3.13 in [7] repeatedly, it can be shown that the last summation actually equals to .…”
Section: Preliminariesmentioning
confidence: 85%
“…In light of the Theorem 3.1, for strongly connected graphs, we can relax the condition on the graph in [8]. In that paper regularity of the underlying graph was assumed to ensure that belongs to the category (see [8] for notation) for the unique KMS state on a strongly connected graph . Now we have for a strongly connected graph (regular or not) with its unique KMS state , the category contains .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation